Sukuk and economic growth: Evidence from panel data - Nayan, Sabri; Kadir, Norsiah (2014)
An active and efficient capital market is crucial in accelerating economic growth in a modern market oriented economy.Capital market provides an alternative funding avenue for firms and government.Capital market instruments provide larger capital amounts as well as liquidity for investors.Sukuk, a relatively new capital market instrument is a certificate which represents the value of an asset.Modern sukuk emerged to fill a gap in the global capital market as an alternative investment.Islamic investors want to balance their equity portfolios with bond-like products.Because sukuk are asset -based securities and not debt instruments, they fit the bill.Presently,Sukuk have been the most active Islamic market instruments in capital markets.There is increasing demand for sukuk instrument in the Islamic countries as well as the rest of the world as an alternative to conventional bonds.Sukuk can promote productive projects through the efficient use of funds and improving the efficiency of resources allocation.At the same time, Sukuk can sustain economic growth, expand employment and reduce poverty. However, the relationship between sukuk and economic growth is still a controversial issue.Therefore,the main motivation of this paper is to investigate the relationship between sukuk and economic growth by employing panel data econometrics technique. Interestingly, the result reveals that sukuk significantly affect and contribute to economic growth.Islamic capital markets in general and sukuk in particular can promote economic growth.